Parents in the face of their children’s death education – attitudes and selected differentiating factors - Agnieszka Zamarian (Studia z Teorii Wychowania)
Intruduction: Nowadays we are dealing with changes in cultural and social reception of death related to its taboo and trivialization. They generate discussion around the need to design and implement intentional activities known as death education. It includes crisis intervention and developmental-preventive education. Crisis intervention relates to providing support in the event of dying or mourning. Developmental-preventive education is focused on building a mature attitude towards one’s own death and that of others before it becomes true. The implementation of death education requires the involvement of various educational environments, including school and family, as well as cooperation between them. From this perspective, parents’ support for death education seems crucial.Method: The research had the following objectives: to create a reliable and valid tool for measuring parents’ attitude towards death education; to describe parents’ attitude towards death education; to determine factors differentiating parents’ attitude towards death education. The study involved 394 parents. They completed a set of questionnaires: The Parents’ Attitude towards Death Education Questionnaire (KRET), the Death Attitude Profile Questionnaire (DAP-R-PL), the Death Fear and Fascination Scale (SLFŚ) and the Personal Experiences Related to Death Scale (SODŚ).Results: The original Questionnaire of Parents’ Attitude towards Death Education (KRET) has a three-factor structure confirmed by confirmatory analyzes (CFA). It consists of the following subscales: 1) the school dimension of death education, 2) the family dimension of death education, 3) the develpomental-preventive dimension of death education. Satisfactory reliability of the subscales has been demonstrated. Correlational analyzes revealed the significant relationships between the KRET subscales and the subscales of the tools which measure general attitude towards death: DAP-R-PL and SLFŚ. It indicates the external (discriminant) validity of the tool. The data obtained by using the KRET suggest that the surveyed parents are relatively opened to all three dimensions of death education, with the family demension being recognized to the gratest extent, the developmental-preventive dimension to a slightly lesser extent, and the school dimension to the least extent. The fators that differentiate the attitude towards death education are: the level of parents’ education and their personal experiences related to death.Conclusions: The research resuluts may be significant for the design and implementation of death education. They provide a reliable and valid tool for measuring parents’ attitude towards death education. They indicate that respondents support all dimensions of death education, which can be considered as preliminary ligitimization of intentional actions in this area. They also identyfy the level of parents’ education and their experiences related to death as factors differentiating the attitude towards death education, pointing to the importance and scope of activities addressed to parents as adult subjects of death education.